Nilai Dakwah Dalam Al-Quran - zumaroh zumaroh zumaroh (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2021)
Islam is religion carry of salvation mission or dakwah for all over nature. For realization that mission, Allah SWT down the Holy Quran for mankind guidance. Yusuf Qordhowi, said in the Al-Quran have two base value dakwah there are correlation with divinity and with society. As for the first value is confession taha Allah SWT is the oneness of the God in the word and the second are: equality and brotherhood, justice and world peace. All of teaching are values of dakwah to be called of humand kind. Tauhid is primary for all of human action must be impacted for social kindness. Therefore, belief in the oneness of god/Allah SWT and deny of toghut will be inflicted for goodness of ummah and actualized Islam rahmatan lilalamin. This research use study text approach, and use library reseach aggregation with conten analysis methode.